Interfacing DNA nanodevices with biology: challenges, solutions and perspectives - Mathias Vinther; Jørgen Kjems (New Journal of Physics, 2016)
The cellular machinery performs millions of complex reactions with extreme precision at nanoscale. From studying these reactions, scientists have become inspired to build artificial nanosized molecular devices with programmed functions. One of the fundamental tools in designing and creating these nanodevices is molecular self-assembly. In nature, deoxyribonucleic acid (DNA) is inarguably one of the most remarkable self-assembling molecules. Governed by the Watson–Crick base-pairing rules, DNA assembles with a structural reliability and predictability based on sequence composition unlike any other complex biological polymer. This consistency has enabled rational design of hundreds of two- and three-dimensional shapes with a molecular precision and homogeneity not preceded by any other known technology at the nanometer scale. During the last two decades, DNA nanotechnology has undergone a rapid evolution pioneered by the work of Nadrian Seeman (Kallenbach et al 1983 Nature http://dx.doi.org/10.1038/305829a0 205 http://dx.doi.org/10.1038/305829a0 ). Especially the introduction of the versatile DNA Origami technique by Rothemund (2006 Nature http://dx.doi.org/10.1038/nature04586 440 http://dx.doi.org/10.1038/nature04586 ) led to an efflorescence of new DNA-based self-assembled nanostructures (Andersen et al 2009 Nature http://dx.doi.org/10.1038/nature07971 459 http://dx.doi.org/10.1038/nature07971 , Douglas et al 2009 Nature http://dx.doi.org/10.1038/nature08016 459 http://dx.doi.org/10.1038/nature08016 , Dietz et al 2009 Science http://dx.doi.org/10.1126/science.1174251 325 http://dx.doi.org/10.1126/science.1174251 , Han et al 2011 Science http://dx.doi.org/10.1126/science.1202998 332 http://dx.doi.org/10.1126/science.1202998 , Iinuma et al 2014 Science http://dx.doi.org/10.1126/science.1250944 344 http://dx.doi.org/10.1126/science.1250944 ), and variations of this technique have contributed to an increasing repertoire of DNA nanostructures (Wei et al 2012 Nature http://dx.doi.org/10.1038/nature11075 485 http://dx.doi.org/10.1038/nature11075 , Ke et al 2012 Science http://dx.doi.org/10.1126/science.1227268 338 http://dx.doi.org/10.1126/science.1227268 , Benson et al 2015 Nature http://dx.doi.org/10.1038/nature14586 523 http://dx.doi.org/10.1038/nature14586 , Zhang et al 2015 Nat. Nanotechnol. http://dx.doi.org/10.1038/nnano.2015.162 10 http://dx.doi.org/10.1038/nnano.2015.162 , Scheible et al 2015 Small http://dx.doi.org/10.1002/smll.201501370 11 http://dx.doi.org/10.1002/smll.201501370 ). These advances have naturally triggered the question: What can these DNA nanostructures be used for? One of the leading proposals of use for DNA nanotechnology has been in biology and biomedicine acting as a molecular ‘nanorobot’ or smart drug interacting with the cellular machinery. In this review, we will explore and examine the perspective of DNA nanotechnology for such use. We summarize which requirements DNA nanostructures must fulfil to function in cellular environments and inside living organisms. In addition, we highlight recent advances in interfacing DNA nanostructures with biology.